Seismic Analysis of High Rise Building Using Inverted V Bracings with ETABS Software - KUMAR, B.NAGA NIRANJAN; KUMAR, DR.M. ASHOK (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Earthquake load is becoming a great concern in our country as because not a single zone can be designated as earthquake resistant zone. One of the most important aspects is to construct a building structure, which can resist the seismic force efficiently. Study is made on the different structural arrangement to find out the most optimized solution to produce an efficient safe earthquake resistant building. The basic principles of design for vertical and lateral loads (wind & seismic) are the same for low, medium or high rise building. The vertical loads increase in direct proportion to the floor area and number of floors. In contrast to this, the effect of lateral loads on a building is not linear and increase rapidly with increase in height. Due to these lateral loads, moments on steel components will be very high. By providing bracing, these moments can be reduced. In the present analysis, 23 Storeys residential building is analyzed with columns, columns with Inverted V bracings at different locations in two different earth quake zones (zone 3 & zone 5) with respect to three soil types. Moments, Base Shear, Displacement, Storey shear were compared for different load combinations. It is observed that the deflection was reduced by providing the Inverted V bracing commercial package ETABS has been utilized for analyzing 23 storey's residential building for different zones. The result has been compared using tables & graph to find out the most optimized solution. Concluding remark has been made on the basis of this analysis & comparison tables